Characteristics of Hybrid Composite from Hydroxyapatite/Metal Powder and Ceramic - Agus Pramono; Fatah Sulaiman; Alfirano Alfirano; Suryana Suryana; Anistasia Milandia (Universitas Sultan Ageng Tirtayasa, 2020)
Milkfish bones/chanos-chanos forsk (CCF) contain of 4% calcium, 3% phosphorus, and 32% protein. CCF is heated at certain temperatures (500-7000C) then can be turned into hydroxyapatite (HAp) as a biomaterial application. The selection of materials in accordance by HAp is aluminum (Al), magnesium (Mg) and titanium (Ti). Al is one of the non-ferrous metals with very wide applications. It has specific properties such as; being light weight, ductile and a lower melting point compared to many other common engineering materials. The combining some of metals by HAp, is a composite material term, which is currently the latest development for processing various elements of different materials. Processing of composite for multi-alloy materials, requires a complex process in resulting of products, both in terms of parameters and process variables. Self-propagating high temperature synthesis (SHS) is a relatively novel and simple method for making certain advanced composites and intermetallic compounds. The SHS method is very suitable to be used as a composite multi-alloy material processing because it has a series of processes capable of producing strong bonds between the elements combined, such as HAp, Al, Mg and Ti. The HAp material from milkfish bones was combined by several metal materials such as Al, Mg and Ti. The use of this material is expected to improve mechanical properties especially eliminating fragility in composite materials. Variation of composition on hybrid composites consist of 3 types: (hybrid composites). There are three combinations of compositions in hybrid composite manufacturing, namely: 80% HAp; 10% Al; 5% Mg; 5% Ti, 80% HAp; 10% Al; 5% Mg; 5% Cu and 80% HAp; 10% Al; 5% Mg; 5% SiC. Characterization carried out ware mechanical and microstructure to determine the properties of hybrid composites, from the values obtained can be recommended for biomaterial applications